Impact of progesterone concentration on human chorionic gonadotropin trigger day on clinical outcomes with one top-quality cleavage-stage embryo or blastocyst transfer in fresh in vitro fertilization cycles - Xu, Jianing; Zhang, Cuilian; Wang, Shuna; Zhang, Shaodi (Frontiers in Endocrinology, 2023)
Objective To investigate the impact of the progesterone concentration on the human chorionic gonadotropin (hCG) trigger day on clinical outcomes with an antagonist protocol. Methods The retrospective cohort study included a total of 1,550 fresh autologous ART cycles with one top-quality embryo transfer. Multivariate regression analysis, curve fitting, and threshold effect analysis were performed. Results A significant association was found between the progesterone concentration and clinical pregnancy rate (adjusted OR, 0.77; 95% CI, 0.62–0.97; P = 0.0234), especially in blastocyst transfer (adjusted OR, 0.56; 95% CI, 0.39–0.78; P = 0.0008). The association between the progesterone concentration and the ongoing pregnancy rate was insignificant. The clinical pregnancy rate showed a linear relationship with an increased progesterone concentration in cleavage-stage embryo transfer. In blastocyst transfer, as the progesterone concentration increased, the clinical and ongoing pregnancy rates showed a parabolic reverse-U curve; the curve initially increased before declining at high progesterone concentrations. The clinical pregnancy rate increased with a progesterone concentration up to 0.80 ng/mL rather than tended to be stable. The clinical pregnancy rate significantly decreased when the progesterone concentration was ≥0.80 ng/mL. Conclusion The progesterone concentration on the hCG trigger day exhibits a curvilinear relationship with pregnancy outcomes in blastocyst transfer cycles, and the optimal threshold of the progesterone concentration is 0.80 ng/mL.